PENGARUH KOMITMEN ORGANISASI DAN KOMPENSASI NON FINANSIAL TERHADAP KINERJA ANGGOTA KOMUNITAS ARSA JAKARTA - Fauzi, Mohammad Reza; Widodo, Sri (JURNAL ILMIAH M-PROGRESS, 2021)
This study aims to determine and prove the effect of organizational commitment and non-financial compensation on the performance of members of the Arsa Jakarta community. This study uses a quantitative approach with a survey method. The population is 165 peoples and the sample is 131 peoples with simple random sampling technique. The data collection method used a questionnaire with a Likert scale of 1 to 5. The method of data analysis used descriptive analysis with Excel software and SPSS version 22. The results showed that (1) Organizational commitment partially had a positive and significant effect on the performance of members of the Arsa Jakarta Community by 20%. (2) Non-financial compensation partially has a positive and significant effect on the performance of members of the Jakarta Arsa Community by 65.9%, (3) Organizational commitment and non-financial compensation simultaneously have a positive and significant effect on the performance of members of the Jakarta Arsa Community by 64.3% , while 35.7% is influenced by other variables not discussed in this study.Keywords: organizational commitment, non-financial compensation, performance